Sequence of Quaternary Sediments in the Bélanger Sand Pit, Pointe-Fortune, Québec-Ontario - Veillette, Jean; Nixon, F. (Géographie physique et Quaternaire, 1984)
ABSTRACTDrilling in the floor of the Bélanger sand pit (Ontario) near Pointe-Fortune, Québec, added 3 stratigraphic units to those already exposed in the pit: a lowermost till, and an intermediate organic-bearing (?) sand-clay unit overlain by a massive lacustrine clay. The subsurface units, comprising about 70% of the stratigraphy, complete the Quaternary sequence exposed in the pit face : an organic-bearing silty sand (>40 000 years BP) unit truncated by an unfos-siliferous sand unit and overlain by the uppermost till. The overall sequence forms a continuous 18 m column of Quaternary sediments. The Pointe-Fortune sequence shows some similarities with the Trois-Rivières Quaternary series which includes the Saint-Pierre sediments >75 000 years old. In addition to stratigraphie information the combination of direct (drilling) and indirect (geophysical) methods of investigation by providing a three-dimensional picture of the subsurface has proved helpful in interpreting the stratigraphy. The geotechnical properties of a massive overconsolidated clay have been determined to facilitate the planning of future subsurface investigation.